2017
DOI: 10.11114/jets.v6i1.2726
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Tuning System and Instrument Variables on Modal Dictation Performance

Abstract: Ear training and musical literacy (ETML) education is one of the main dimensions of the bachelor degree program of music teacher education departments, which provides professional music education. In ETML education, hearing, sight-reading and dictation studies for Turkish music makams have an important place. In this study, it was aimed to investigate the effects of different instrument sources and tuning systems; namely, equal tempered or traditionally tempered, on the modal dictation performances of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It seems that relations between dictation and singing back, like those discussed in this section, may be explained by the vocal timbre, because it favors the memorization of musical patterns, facilitating its recovering and identification in the music to be dictated, thus improving subjects’ responses. This assumption is supported by Radvansky and Potter (2000), who observed that melody memorization is affected by the timbre in which the music is played, by Vanzella et al (2014), according to whom the human voice is a timbre that favors musical memorization, and by Taube (2006), González et al (2015) and Demirbatır et al (2018), who verified that different timbres can lead to different levels of success in dictation taking.…”
Section: Singing Back and Dictation Takingmentioning
confidence: 88%
“…It seems that relations between dictation and singing back, like those discussed in this section, may be explained by the vocal timbre, because it favors the memorization of musical patterns, facilitating its recovering and identification in the music to be dictated, thus improving subjects’ responses. This assumption is supported by Radvansky and Potter (2000), who observed that melody memorization is affected by the timbre in which the music is played, by Vanzella et al (2014), according to whom the human voice is a timbre that favors musical memorization, and by Taube (2006), González et al (2015) and Demirbatır et al (2018), who verified that different timbres can lead to different levels of success in dictation taking.…”
Section: Singing Back and Dictation Takingmentioning
confidence: 88%
“…Another study shows that high school GPA impacts the university GPA greater than pre-university tests, and enrolled year has a surprising effect on the university GPA (Hassan & Al-Razgan, 2016). Another study shows that there is a positive correlation between the musical aptitude exam scores and freshman year GPAs of the students (Demirbatir et al, 2015).…”
Section: Literature Study and Methodsmentioning
confidence: 98%